Ang batang natutong gumising ng maaga (The child who rises early) - Villanueva, Rene O. (Lampara books, 2006)
"The sun wakes up at the same time as Mister Rooster. Madam meow has also risen to suckle her kittens. Mommy trush and daddy trush have taken off to search for food for their fledglings. Brother jeep and mister bus are also up to bring employees to their offices. Everyone is up and about--except Budoy who is still snoring in bed. No wonder he is late for school again! Grandfather Uban tells the story of how a boy who wakes up early is never in a hurry, is never left behind and accomplishes more in a day."